Edukasi Simulasi Multi-Bencana terhadap Kesiapsiagaan Siswa SMKN 1 Galang - Rahmat Kurniawan; Saman Saman; Baharuddin Condeng; Hamsiah Hamsiah; Zainul Zainul; Putri Handayani; Amir Amir; Arifuddin Arifuddin (Universitas Baiturrahim, 2026)
Disaster preparedness among school students is an important aspect of disaster risk reduction efforts. This community service activity ims to increase the knowledge and attitude of SMKN 1 Galang students regarding disaster preparedness through multi-disaster simulation education. The method used is participatory education through interactive lectures, visual media, and disaster simulations covering earthquakes, floods, landslides, and fires, with a pre-test and post-test design. The activity was carried out in December 2025, involving 40 students as participants. The results showed an increase in students' knowledge and preparedness attitudes, where before the intervention, most respondents were in the “poor” category, while after the intervention, all respondents (100%) were in the “good” category. Multi-disaster simulation education proved effective in increasing student preparedness and is recommended as a school-based disaster education model to build a sustainable disaster preparedness culture.